Do environmental policies matter for productivity growth? Insights from new cross-country measures of environmental policies - Albrizio, Silvia; Botta, Enrico; Kozluk, Tomasz; Zipperer, Vera (Paris, 2014)
"Environmental policies address wellbeing and sustainability objectives, affecting firm and household behaviour. A newly developed, cross-country composite proxy of environmental policy stringency (EPS) shows that stringency has been increasing across OECD countries over the past two decades. However, the tightening environmental policies have had little effect on aggregate productivity, spurring primarily short-term adjustments. Nevertheless, they have led to various effects within the economy - the most technologically advanced industries and firms have seen a small increase in productivity, possibly being in the best position to adapt. Least productive firms have seen their productivity fall. Part of the effect is likely to have taken place through entry and exit of firms and relocation of activities. Finally, this project provides evidence on the anti-competitive bias of some aspects of environmental policies. The indicator of Burdens on the Economy due to Environmental Policies (BEEP) shows that barriers to entry and competition, and the consideration given to economic effects of environmental policies vary notably across countries, but that this variation is not related to the stringency of policies. Hence, to support both economic and environmental outcomes, stringent environmental policies can and should be implemented with minimum barriers to entry and competition."